The Influence Of Work Discipline And Leadership Style On Teacher Performance At Sma Negeri 1 Tanjng Tebat - Nabela, Ina; Markus, Markus; Sholiha, Mila (Universitas Dehasen Bengkulu, 2025)
consisting of 62 teachers, 20 (twenty) teachers, and 6 (eight) teachers. The sample in this study consisted of 42 teachers at SMA Negeri 1 Tanjung Tebat. The t-test value for the variable